2020
DOI: 10.1186/s12904-020-0529-z
|View full text |Cite
|
Sign up to set email alerts
|

When a child dies: a systematic review of well-defined parent-focused bereavement interventions and their alignment with grief- and loss theories

Abstract: Background: The availability of interventions for bereaved parents have increased. However, most are practice based. To enhance the implementation of bereavement care for parents, an overview of interventions which are replicable and evidence-based are needed. The aim of this review is to provide an overview of well-defined bereavement interventions, focused on the parents, and delivered by regular health care professionals. Also, we explore the alignment between the interventions identified and the concepts c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 66 publications
(132 reference statements)
2
59
0
10
Order By: Relevance
“…Similarly, most developed bereavement interventions are aimed at supporting parents after the death of their child. 4,5,17 However, the importance of aiding parents in their coping with grief prior to their child's death is becoming more evident in research and in theories on loss and grief. 7,18,19 Theories emphasize that bereaved parents have to adjust to a 'new reality' where the child is physically absent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, most developed bereavement interventions are aimed at supporting parents after the death of their child. 4,5,17 However, the importance of aiding parents in their coping with grief prior to their child's death is becoming more evident in research and in theories on loss and grief. 7,18,19 Theories emphasize that bereaved parents have to adjust to a 'new reality' where the child is physically absent.…”
Section: Discussionmentioning
confidence: 99%
“…In order to make this transition parents have to cope with several conflicting emotions, to eventually adjust their plans and integrate the loss in their autobiographical memory. 4,[20][21][22][23] An important aspect of this adjustment, that characterizes the process of bereavement, are two components of anticipatory grief; 7,24 preparedness and awareness time on the impending death. 25,26 Studies have shown that HCPs are able to positively influence parental preparedness by conducting end-of-life conversations, in which topics such as prognoses, future scenario's, and grief and loss are discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the infant dies, there will be no decisional burden for the parents to bear. While in the NICU, memory-making will take place (pictures, visits from extended family, rituals at parental discretion), acknowledging the infant's place in the family narrative, all of which may lessen the burden of bereavement if the baby dies (Kochen et al 2020).…”
Section: Postponed Withholding In Practicementioning
confidence: 99%
“…When parents experience the death of a child, no matter the age, they experience a range of complex, often intolerably painful emotions [1]. The experience and effects of the death of a child on parents has received considerable attention, including the psychosocial impacts experienced as a consequence of devastating and enduring grief [2]; the experience of parents around end of life of a child [3][4][5]; what they want and expect from healthcare practitioners (HCPs) [2,6]; and impacts of bereavement services and interventions [1,7]. Less work has focused on the communication remembered by parents as part of their experiences of care or services received, or how that communication subsequently scaffolds their experience of bereavement.…”
Section: Introductionmentioning
confidence: 99%